International Conference on Applied Life Sciences - Nejadkoorki, Farhad (IntechOpen, 2012)
The International Society for Applied Life Sciences (ISALS) is a worldwide Organization that aims to help scientists and researchers, publish recent findings in its scientific journals, and conferences as well as consultancy services it may provide. The society is being run by a team of highly professionals all around the world. You are welcome to join the society and contribute to improve it.